Ila Hadal Walaal: A Traditional Reconciliation Model for Healing Somalia's Wounds - Hersi, Abdullahi Mohamed (Indonesian Journal of Social Science Research, 2023)
Reconciliation involves rebuilding relationships among people and groups in society and between the state and its citizens. The protracted conflict in Somalia had devastating effects on Somali citizens. Formulating a genuine social reconciliation model that can contribute to trauma healing, trust building, and an enabled environment for forgiveness and sharing narratives continues to pose daunting challenges to peace and state-building in Somalia. This paper provides analytical thinking by coalescing traditional Somali reconciliation approaches and modern peace-building principles. It attempts to establish a new model based on Somali cultural norms and values. The paper pinpoints the legal, institutional, and political issues that are prerequisite for any viable and successful social reconciliation. It recommends capacity development of public institutions mandated to facilitate and oversee national, regional, and local reconciliation exercises while underscoring the pivotal role of women and other members of civil society.